2014
DOI: 10.3892/ol.2014.2089
|View full text |Cite
|
Sign up to set email alerts
|

Malignant neoplasia arising from ovarian remnants following bilateral salpingo-oophorectomy (Review)

Abstract: Ovarian remnant syndrome (ORS) is a rare, but well-known gynecological complication, most often induced by difficult bilateral salpingo-oophorectomy (BSO) procedures that leave residual ovarian tissue on the pelvic wall. The most common preexisting conditions for this complication include endometriosis, pelvic inflammatory disease and prior abdominal surgery. The residual ovarian tissue may eventually cause malignant development. A total of 12 cases of malignant and benign tumors (clear cell adenocarcinoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] In addition, clinicians might have consensus that sometimes it is hard to totally eradicate all visible or invisible lesions, including ovarian tissues, especially when the certain situations exist, such as deep infiltration endometriosis, severe adhesion between ovary and surrounding pelvic tissue or organs, which will make a total removal of ovary difficult (remnant ovarian syndrome). [102][103][104][105] Moreover, these disparate results suggest that the different histology types of benign ovarian tumors should be considered in studies that examine the influence on EOC risk. 80 As shown above, our results indicated that the initial procedure of ovarian surgery may not be associated with the decreased risk of subsequent development of EOC, even though BO or BSO was performed at the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] In addition, clinicians might have consensus that sometimes it is hard to totally eradicate all visible or invisible lesions, including ovarian tissues, especially when the certain situations exist, such as deep infiltration endometriosis, severe adhesion between ovary and surrounding pelvic tissue or organs, which will make a total removal of ovary difficult (remnant ovarian syndrome). [102][103][104][105] Moreover, these disparate results suggest that the different histology types of benign ovarian tumors should be considered in studies that examine the influence on EOC risk. 80 As shown above, our results indicated that the initial procedure of ovarian surgery may not be associated with the decreased risk of subsequent development of EOC, even though BO or BSO was performed at the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The process can occur as a result of the metastasis process or as a result of a process called Ovarian Remnant Syndrome (ORS), which occurs as a result of excision of the incomeplete from ovarian carcinoma tissue. According to Imai A, Matsunami K, Takagi H et al (2014), 6 incidence of ORS generally occurs within a median of 12-13 years (range of 2-54 years). The way to differentiate postoperative pelvic/abdominal tumor lesions/chemotherapy ovarian carcinoma is to use tissue histology and FSH concentration.…”
Section: Discussionmentioning
confidence: 99%
“…FSH concentrations < 40 mIU/ml in patients who got the BSO procedure can lead to the diagnosis of ORS (In this patient, post-debulking histological tissue examination for the indications of the finding of tumor cell infiltration on the pelvis produced a result in the form of cystadenoma serosum papiliferum). 6 The examination of grade tumor also helps in knowing the prognosis of patients with ovarian carcinoma as a result of this examination, which reflects on the biology of the tumor cells. According to Ezzati M. et al (2014), 1 high-grade tumor tend to have a worse prognosis compared to low-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian remnant syndrome (ORS), a rare phenomenon where ovarian tissue remains in the pelvic cavity after a BSO, is an important complication to be aware of . The risk of ORS increases during challenging BSO's such as in patients with endometriosis, which can impair visibility and make it difficult to completely remove the ovaries . In such scenarios, ovarian tissue can adhere to the pelvic wall and ectopically implant in surrounding tissue, and can eventually produce hormones …”
Section: Introductionmentioning
confidence: 99%
“…The risk of ORS increases during challenging BSO's such as in patients with endometriosis, which can impair visibility and make it difficult to completely remove the ovaries . In such scenarios, ovarian tissue can adhere to the pelvic wall and ectopically implant in surrounding tissue, and can eventually produce hormones …”
Section: Introductionmentioning
confidence: 99%